Trade and Poverty in EU Regions : An Empirical Analysis - Signoret, José (World Bank, Washington, DC, 2020)
This study builds on recent efforts by the World Bank and the European Commission in generating detailed poverty estimates at detailed subnational levels (the EU Poverty Map). This information is combined with estimates of subnational trade flow data for subnational regions between 2000-2010, as well as information on country and regional characteristics. Poverty estimates from the EU Poverty Map refers to a relative concept of poverty, measuring the share of population below a country-specific low-income threshold. This notion of relative poverty can be informative of disparities in welfare gains within countries often associated with trade, especially given the current backlash on globalization from the perception that it may leave some segments of the population behind. The negative relationship between poverty and trade is observed when both import and export openness are considered individually, but it arises more clearly in the case of export orientation. Export orientation can be associated with lower levels of poverty particularly in the poorest regions. The relationship between import exposure and poverty rates is not significant. Additional analyses show that export openness is more strongly linked to lower poverty in regions where production tends to be more ‘low-tech’. All together, these results suggest that both exports and imports are associated to lower poverty, but especially when it relates to higher export opportunities in poorer regions and where production is concentrated in relatively labor-intensive goods. While this analysis does not consider micro-level effects such as at the enterprise or household level that could possibly show greater heterogeneity, the results suggest that cross-country estimates in the literature that show a positive effect of trade openness on economic performance tend to hold at subnational regional levels in the EU. Overall, this study shows that poverty and the relative concentrations of poor people in the EU is an issue that policymakers should put high on the agenda. Opening markets and creating a more level playing field in global markets for export opportunities is critical for regional development. For certain regions however, policies to support the transition and the mitigation of transition costs may be necessary. While the empirical evidence is still building up, whether this assistance should be industry-based, versus locality based, is an important distinction, as trade shock effects seems to matter more by locality than by industry.